The technique of Islamic bookbinding : methods, materials and regional varieties - Scheper, Karin. (Islamic Manuscripts and Books, 2015)
The Technique of Islamic Bookbinding is the first monograph dedicated to the technical development of the bookbinding tradition in the Islamic world. Based on an assessment of the extensive oriental collections in the Leiden University Library, the various sewing techniques, constructions and the application of covering materials are described in great detail. A comparative analysis of the historic treatises on bookbinding provides further insight into the actual making of the Islamic book. In addition, it is demonstrated that variations in time and place can be established with the help of distinctive material characteristics. Karin Scheper's work refutes the perception of Islamic bookbinding as a weak structure, which has generally but erroneously been typified as a case-binding. Instead, the author argues how diverse methods were used to create sound structures, thus fundamentally challenging our understanding of the Islamic bookbinding practice. Karin Scheper has been awarded the De La Court Award 2016 by The Royal Netherlands Academy of Arts and Sciences for her study of the bookbinding tradition in the Islamic world.